Analytic Research about the Exegetic Attitudes of Abu l-Qāsim al-Ka'bi al-Balkhı̄ - Hasan Kharaghani; Ali Akbar Rostami; Sayyed Muhammad Ali Fahimi (آموزه‌های قرآنی)
The science of the exegesis is owed to the exegetes’ attempts which have interpreted and determined the Book of Almighty. Some of these exegeses have been vanished but the opinions of their authors in some of the verses have been remained. Of these groups is Abu l-Qāsim al-Ka'bi al-Balkhı̄ who was a muʿtazilah theologian and exegete. This paper with analytic-descriptive method studies some of his opinions in the exegesis and it clears that he interpreted the Quran verses with the Quranic-rational method and he attached much important to know the intent of God for the linguistic sense (siaq) and interpretative nuances. Therefore, the aim of the words which was tested Ibrahim prophet (peace be upon him) is imāmah (Arabic: إمامة‎) which God completed and fulfilled. Also in sūrah al-Qiyamah (Arabic: القیامة‎), he put aside the well-known opinion and he thought that the meaning of the Quran is the recitation of his record. The intellectual and theological arguments in his resulting precepts have a special position and according to it he believes that Adam is Qibla and not being prostrated by the angels and Adam’s heaven being earthy and he does not believe in the World of Pre-Existence (Alam-e-Zar) and the intellects of human beings is the declaration of faith inthe Deity (God). And also the government and the vicegerency which are the covenant of Allah is not legitimate for the aggressors and disbelievers. Qiraʼat and fiqh al-Quran are of his exegetic chapter titles.